Analysis of Education Report Card Utilization for School Quality Mapping Via Deming Cycle - Indartik, Enik; Zuriah, Nurul; Restian, Arina (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This research analyzes the utilization of the Education Report in mapping and improving school quality using the Deming Cycle approach at Vocational High Schools (SMK) in Mojokerto Regency. The study is motivated by the necessity for schools to adopt a data-based quality management system that supports planning, implementation, evaluation, and continuous quality improvement. This study employs a qualitative approach with a multisite research design. The research subjects consist of the school principals, deputy principals in charge of curriculum, student affairs, facilities and infrastructure, public relations and industry relations, as well as administrative coordinators at State Vocational High School 1 Punging, State Vocational High School 1 Trowulan, and State Vocational High School NU Ma'arif Jatirejo. Data collection involved in-depth interviews, direct observations, and documentation studies of planning and school quality reports. Data analysis followed the stages of data reduction, data presentation, and conclusion drawing, applying source triangulation to ensure data validity. The findings indicate that the Education Report serves as a foundation for developing school program planning, implementing quality improvement activities, evaluating school performance, and preparing for continuous follow-up improvements. The application of the Deming Cycle encourages schools to make data-based decisions and strengthen their internal quality management systems. Supporting factors for implementation include the commitment of school leadership, active involvement of the management team, and the availability of integrated quality data. Inhibiting factors include limited facilities and infrastructure for practice, differences in human resource competencies, and suboptimal utilization of quality data across all work units. This study concludes that integrating the Education Report with the Deming Cycle approach is effective in supporting systematic and continuous mapping and improvement of SMK quality.